The influence of CO2 accelerated carbonation on alkali-activated fly ash cement under elevated temperature and pressure: Einfluss von CO2 beschleunigter Karbonisierung auf alkalisch aktivierten Flugaschezement unter erhöhter Temperatur und erhöhtem Druck - Ridha, S. (Wiley-VCH Verlag, 2018)
An alternative of wellbore cement system, formed through alkali-activation of fly ashes also knows as fly ash geopolymers, provides attractive properties due to its high compressive strength and durability against acidic conditions. However, changes in microstructure and mineralogical during accelerated carbonation affected by CO2 alteration under elevated temperature and pressure have not been fully understood. This paper investigates and characterizes the alkali-activated binders fly ash based in the acidic environment under elevated temperature and pressure. The results found that scales such a layer was formed in the gel phase at the spherical surface of fly ash after carbonation process. The effect is that the surface of the gel phase became rough and porous. Carbonate and/or bicarbonate salts were identified as major phase in the sample after immersion test. In the activated fly ash cement, both calcium aluminate silicate hydrate (CâAâSâH) and sodium aluminosilicate hydrate (NâAâSâH) gels were formed; CâAâSâH gel was decalcified, forming calcium carbonate phase in the form of calcite, aragonite or vaterite. These findings were confirmed by the analysis and identification of Fourier-transformed infrared spectroscopy, X-ray diffraction and scanning electron microscopy tests on the changes in the cement system. Â© 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim